Au Multimer@MoS2 hybrid structures for efficient photocatalytical hydrogen production via strongly plasmonic coupling effect. (December 2016) - Li, Xuanhua; Guo, Shaohui; Kan, Caixia; Zhu, Jinmeng; Tong, Tengteng; Ke, Shanlin; Choy, Wallace C.H.; Wei, Bingqing
Abstract: Photocatalytical water splitting of MoS2 nanomaterials based on plasmonic nanoparticles (NPs) has been limited because of the insufficient utilization of plasmonic hot spots, which is an important strategy for efficient light harvesting. Here, we design a high-performance photocatalyst Au multimer@MoS2 core-shell hybrid structures to address this issue. The Au NP's multimer with 5–10 nm inter-particle distance realized by a pre-decoration is employed as a plasmonic component. As expected, rationally structural arrangement provides a strong near-field coupling at their inter-particle gaps of Au NPs and then gives rise to strong absorption enhancement, which leads to the significant improvement of exciton generation and dissociation in the Au-MoS2 junctions. Theoretical modeling and surface enhanced Raman scattering (SERS) have been used to demonstrate the enhanced optical effect; and the photoluminescence (PL) and electrochemical measurements are adopted to clarify the improved electrical effect. As a result, a 240.2% increment in hydrogen gas production amount (2997.2 μmol/g) is achieved as compared to that of the pure MoS2 spheres (881.6 μmol/g). The hydrogen gas production amount of Au multimer@MoS2 spheres is among the highest values reported in the plasmon-enhanced photocatalytic hydrogen production. Graphical abstract: Highlights: Integration of Au multimer with 5–10 nm gap with MoS2 spheres is synthesized. Strong near-field coupling in multimer improves exciton generation and dissociation. A 240% increment in hydrogen gas production for Au multimer@MoS2 hybrid is achieved.